Determinação das castas em Scaptotrigona postica (Latreille) (Hymenoptera, Apidae, Meliponini): diferenciação do ovário - Santos, Thaís da Cruz Alves dos [UNESP]; Cruz-Landim, Carminda da [UNESP] (Sociedade Brasileira de Zoologia, 2002)
Both castes of Scaptotrigolia postica (Latreille, 1804) possess four ovarioles in each ovary. Queen and workers have the same ovarian development during the larvallife, but in lhe late larval stage the queen ovary beco me larger. During pupation a higher rate of cell division is observed in queen ovarioles and a higher rale of cell death in workers. Newly emerged workers have short ovarioles with differenriatcd germarium and vitellarium while queens have very long ovarioles with only germarium. Caste deterrnination in rhis species of bee is trophic, but lhe food does not differ in quality, only in quantiry. The food differences only beco me effecri ve by the end of larval stage when the queen larvae have lhe opportunity of eat more. In this way lhe ovary differentiation, between workers and queens. In this species, only occurs frorn lhe end of larval stage, mainly during pupation. Although the ovaries of workers are smaller, they are precocious in relation to queens, since nurse workers, 5 10 20 days, old may lay eggs. The eggs laid by the workers may be trophic or functional. These eggs may be distinguished by lhe aspect ofthe yolk. Older forager workers have degenerated ovaries.
Caste determination in Scaptotrigona postica (Latreille) (Hymenoptera, Apidae, Meliponini): the ovarian differentiation
Keywords: Stingless beco castes; ovary differentiation; cell division; cell dearh